Squatters and land rights in the formation of “pueblos de españoles” (Rincón de San Pedro, Buenos Aires, 1740-1860) (Quinto Sol, 2015)
During the 18th century, the presence of “pueblos de españoles” and “villas” was multiplied in the Hispano-American Southern border. The importance of squatters in the formation of “pueblos de españoles” was more frequent in Buenos Aires countryside than in other jurisdictions, although little is known on its behavior. The objective of the article is to analyze the leeway for action of squatters to ask for legal land recognition for founding a town in Buenos Aires, to identify the mechanisms used and the difficulties found during the 18th and 19th centuries. The analysis of the case of the town of San Pedro allowed to pose several questions on the characteristics of the regulation of land rights particularly in towns and villages in a period that is often linked to changes in the rights and power relationships exercised in their implementation.
Keywords: “pueblos de españoles”; squatters; land rights; power relationships